Strategic and leading dominants of overcoming economic and managerial deviations of construction projects using the cost engineering method - Bind, V.E.; Revunov, О.М.; Gizhko, A.P.; Grigorenko, V.V.; Malashkin, M.A. (Ways to Improve Construction Efficiency, 2020)
This article is devoted to the development of a conceptual, theoretical-methodological and methodological-applied base for the application of value engineering in construction projects, the use and development of polycriteria systems of value engineering in the activities of construction enterprises. The proposed multi-vector assessment approach will modernize the concept of the content and essence of the operating system of an investment and construction project as a mobile enterprise, proposing new business display subsystems: construction and technological; a subsystem for initiating an investment and construction project, planning and diagnostics; a subsystem of administration, coordination and support. Identification of the state and prospects for the activities of construction enterprises on the basis of value engineering serves as the basis for the development of further measures to improve the efficiency of their functioning, increase the level of competitiveness, investment attractiveness, and create prerequisites for ensuring development. The results of the work will help the top management of contracting enterprises to carry out effective monitoring, structuring and maneuvering the assets of contracting construction enterprises in the process of their operating activities, will give a reasonable opportunity to adjust the economic strategy and parameters of the production and economic portfolio of construction enterprises. Cost engineering in the article means methods of product improvement, organizational services and production technologies, the essence of which is the organizational procedure of finding the optimal ratio between the usefulness of the product and the cost of its creation, improvement and use. The main advantages of the cost engineering system are: reduction of risks for the organization; growth of advantages in domestic and foreign markets; reduction of terms of performance of works and the incurred expenses; increase in return on investment, due to the emergence of levers of influence on the project budget.